2013
DOI: 10.1364/oe.21.030911
|View full text |Cite
|
Sign up to set email alerts
|

Twin-resonance-coupling and high sensitivity sensing characteristics of a selectively fluid-filled microstructured optical fiber

Abstract: A twin-resonance-coupling phenomenon and the sensing characteristics of a selectively fluid-filled microstructured optical fiber (SFMOF) are proposed and demonstrated. The SFMOF is realized by selectively infiltrating refractive index fluid into a single air hole located at the second ring near the core of the MOF. Twin-resonance dips are observed in the transmission spectrum. Theoretical and experimental investigations reveal that the twin-resonance dips both result from the coupling between LP(01)(C) silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Huang et al [33] proposed a unique method for selectively filling the all cladding holes as well as micro core holes. The fabrication of PCF with liquid filled core or cladding can be accomplished with the same method [34,35]. Now, applying the sol-gel technique [36] any kind of complexity of fabrication of microstructure optical fiber can be removed.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al [33] proposed a unique method for selectively filling the all cladding holes as well as micro core holes. The fabrication of PCF with liquid filled core or cladding can be accomplished with the same method [34,35]. Now, applying the sol-gel technique [36] any kind of complexity of fabrication of microstructure optical fiber can be removed.…”
Section: Resultsmentioning
confidence: 99%
“…In the filling process, pressure can be put on the UV-curable polymer within the PCF. Luo et al [29] and Gerosa et al [30] have recently demonstrated experimentally that there can be efficient fabrication of the PCF structures with liquid filled cladding/core holes with the help of identical techniques. For this purpose, the PCF structure suggested in this paper can be fabricated with the existing nanotechnology which shows substantial benefits with respect to important sensor features, for instance high sensitivity, high birefringence, and fewer confinement losses.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The high temperature sensitivity is mainly attributed to the high thermal-optic coefficient (−3.96 × 10 −4 / • C) of the index matching liquid, which affect the self-imaging wavelength efficiently through introducing large surrounding RI change of the HCCW during the temperature test. Of course, the proposed sensor exhibits limited sensitivity in temperature and RI sensing compared to the reported ultra-sensitive structures, such as that of employing waveguide coupling [4,5]. However, it is still meaningful to introduce the self-imaging effect in a HCCW into the fields of fiber optic sensing, because more fiber sensors and devices, especially with the integration of optical functional materials, can be expected to be designed and demonstrated with improved performances and novel applications.…”
Section: Sensing Characteristicsmentioning
confidence: 99%
“…Numerous fiber-optic sensors based upon various operation mechanisms have been reported previously. For example, by means of employing fiber gratings [1], Mach-Zehnder interferometer [2], surface plasmon resonance [3], and photonic crystal fibers [4,5]. Unfortunately, the implementation of these structures often requires complex and time-consuming manufacturing processes, sophisticated processing equipment, or the use of expensive specialty fibers, which may greatly limit the mass production and economics of these devices.…”
Section: Introductionmentioning
confidence: 99%